2005
DOI: 10.1038/sj.emboj.7600800
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the interaction of Bordetella pertussis adenylyl cyclase toxin with calmodulin

Abstract: CyaA is crucial for colonization by Bordetella pertussis, the etiologic agent of whooping cough. Here we report crystal structures of the adenylyl cyclase domain (ACD) of CyaA with the C-terminal domain of calmodulin. Four discrete regions of CyaA bind calcium-loaded calmodulin with a large buried contact surface. Of those, a tryptophan residue (W242) at an a-helix of CyaA makes extensive contacts with the calcium-induced, hydrophobic pocket of calmodulin. Mutagenic analyses show that all four regions of CyaA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
252
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(268 citation statements)
references
References 57 publications
(88 reference statements)
16
252
0
Order By: Relevance
“…Yet strong experimental evidence in favor of this model was provided by the observation that the TUA compounds were also able to inhibit the related adenylyl cyclase from B. pertussis, CyaA. Catalytic domains of CyaA and EF only share 25% overall sequence identity, and the structural and thermodynamic features of their interaction with CaM differ significantly (32,43). Analysis of EF pockets (Table 1) revealed that the catalytic site and the SABC pocket and/or its SBC extension were the only ones to share significant homology with their CyaA counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Yet strong experimental evidence in favor of this model was provided by the observation that the TUA compounds were also able to inhibit the related adenylyl cyclase from B. pertussis, CyaA. Catalytic domains of CyaA and EF only share 25% overall sequence identity, and the structural and thermodynamic features of their interaction with CaM differ significantly (32,43). Analysis of EF pockets (Table 1) revealed that the catalytic site and the SABC pocket and/or its SBC extension were the only ones to share significant homology with their CyaA counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…CyaA is also activated by CaM and the structure of its catalytic site is highly similar to that of EF despite a low overall sequence homology (32). The compounds inhibited CyaA-CaM at 100 μM, but not at 10 μM, indicating that they were moderate inhibitors.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…For this purpose, we employed the BACTH method (bacterial adenylate cyclase two-hybrid) (Karimova et al, 1998), a widely used genetic approach for monitoring protein-protein interactions (Stynen et al, 2012). This assay reconstitutes Bordetella pertussis CyaA activity from trypsin-defined amino-terminal and carboxyl-terminal subdomains of 25 and 18 kDa, respectively (Guo et al, 2005). Interaction between T25 and T18 hybrid proteins generates cAMP, which activates lacZYA operon expression in an E. coli Dcya host strain lacking endogenous adenylate cyclase activity (Brickman et al, 1973).…”
Section: Introductionmentioning
confidence: 99%